PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING DENGAN MEDIA LKS UNTUK MENINGKATKAN KERJASAMA DANHASIL BELAJAR KIMIA SISWA - Feri Andi Syuhada; Makharany Dalimunthe; Wildany Sari Novian Sari; Junifa Layla Sihombing (JS (JURNAL SEKOLAH), 2020)
Abstract: Application of the Contextual Teaching and Learning Model with LKS Media to Increase the Collaboration and Student Learning Outcomes in Chemistry. The population in this study were all students of class X MIA semester II of SMA N 1 Namorambe consisting of 2 classes with a total of 60 students. The sampling used was total sampling method. The instrument used in this study was two domains, namely cognitive test instruments in the form of 12 objective test questions and affective questionnaires in the form of student cooperation attitudes which has been validated. The results of this study obtained an average value of the control class is 80.25 and the experimental class is 81.94. Through the independent sample t-test, a significance value of 0.260 > 0.05 is obtained, then Ho is accepted and Ha is rejected. In increasing learning outcomes obtained an average control class gain of 57.37 % and the average value of the experimental class gain of 64.31 %. T-test results using independent sample t-test, obtained a significance value of 0.0415 > 0.05 then Ha is accepted and Ho is rejected. Keyword:Contextual Teaching and Learningmodel, LKS, cooperative attitude, learning outcomes Abstrak: Penerapan Model Pembelajaran Contextual Teaching and Learning dengan Media LKS untuk Meningkatkan Kerjasama danHasil Belajar Kimia Siswa.Populasi dalam penelitian ini adalah seluruh siswa kelas X MIA Semester II SMA N 1 Namorambe yang terdiri dari 2kelas dengan jumlah keseluruhan siswa 60 orang.Pengambilan sampel dilakukan dengan cara sampling total. Instrumen yang digunakan pada penelitian ini menggunakan dua ranah, yaitu kognitif berupa instrumen tes berupa tes objektif sebanyak 12 soal dan afektif berupa angket sikap kerjasama siswa yang telah divalidasi.Dari hasil penelitian yang diberikan perlakuan berbeda, diperoleh nilai rata-rata kelas kontrol sebesar 80.25 dan kelas eksperimen 81.94. Melalui uji independent sample t-tes diperoleh nilai signifikansi sebesar 0.260 > 0.05, maka Ho diterima dan Ha ditolak. Pada peningkatan hasil belajar diperoleh rata-ratagain kelas kontrol sebesar 57.37%dan nilai rata-rata gain kelas eksperimen  sebesar 64.31%. Hasil uji t  menggunakan independent sample t-test, diperoleh nilai signifikansi= 0.0415> 0.05 maka Ha diterima dan Ho ditolak.  Kata Kunci: Model pembelajaran Contextual Teaching and Learning,LKS, sikap kerjasama, Hasil Belajar Kimia